Structural breaks, cointegration and the Fisher effect - Andreas Beyer; Alfred A. Haug; William G. Dewald (European Central Bank (ECB), 2009)
There is scant empirical support in the literature for the Fisher effect in the long run, though it is often assumed in theoretical models. We argue that a break in the cointegrating relation introduces a spurious unit root that leads to a rejection of cointegration. We applied new break tests and tested for nonlinearity in the cointegrating relation with post-war data for 15 countries. Our empirical results support cointegration, after accounting for breaks, and a linear Fisher relation in the long run. This is in contrast to several recent studies that found no support for linear cointegration.
Keywords: E43; C32; 330; Fisher effect; linear and nonlinear cointegration; Structural change; Fisher-Effekt; Kointegration; Strukturbruch; Verbraucherpreisindex; OECD-Staaten